IDENTIFIKASI SENYAWA KIMIA DAN UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETIL ASETAT BIJI SIRSAK (Annona mucicata Linn.) - Anindini Winda Amalia; Atmira Sariwati (JCPS (Journal of Current Pharmaceutical Sciences), 2019)
Antioxidants are substances that are useful for fighting free radicals. Plants can produce antioxidants to control the oxidative stress.Soursop plants are one of the plants that are known to contain antioxidant flavonoids. The purpose of this study was to determine the content of chemical compounds and antioxidant activity of ethyl acetate extract of soursop seeds. Identification of the content of chemical compounds was carried out qualitatively and quantitatively, while the antioxidant test was carried out using the capture method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals with ascorbic acid as a comparison. The results showed that the soursop seeds ethyl acetate extract contained flavonoids, alkaloids, and saponins, while the results of the quantitative total phenolic and total flavonoid tests were 28.21 ± 0.03 mg/g and 22.17 ± 0.05 mg/g respectively. DPPH results of soursop seeds ethyl acetate extract were 39.45%. These results show that the soursop ethyl acetate extract has a weak antioxidant activity compared to gallic acid. Keywords: soursop seed extract, chemical identification, antioxidants, ethyl acetate, DPPH